THE EFFECT OF USING AUDIOVISUAL MEDIA TOWARD STUDENTS SPEAKING ABILITY AT 12TH GRADE OF PPAY - Syafitri, Riza (BiCED Proceeding, 2024)
This research was motivated by a number of problems that have been plaguing the oral communication skills of students in the twelfth grade at Pondok Pesantren Ashabul Yamin. The study was of a pre-experimental nature, and it consisted of assigning a pre-test and a post-test to a single group of participants. In Pondok Pesantren Ashabul Yamin, there are two classes of students in the twelfth grade. The data for this study came from class XII-1, which was chosen using the Lilliefors test to determine whether or not the data was representative of the whole. On the other hand, the researcher used non-probability sampling in order to test the hypothesis. After that, the researcher consulted the result with the degree table, which is equal to 0.50 per cent. It was confirmed by the findings of the research that the students had low scores on the speaking ability tests that they had taken before the research. As a result of their findings, the researchers came to the conclusion that the utilization of audiovisual media could potentially enhance the students' ability to articulate their thoughts on text taken from news articles. The evidence that was provided by the data obtained from the pre- and post-tests that were given to the 38 students who took part in the study was very convincing. The score of 12,000 on the post-test was much higher than the score of 9,580,000 on the pre-test. Following the test, the standard deviation was found to be 1,090, whereas the standard deviation before the test was found to be 1,348. The acceptance of the alternative hypothesis (Ha) and the rejection of the null hypothesis (Ho) are both indicated by research findings that are less than 0.001. Under the conditions that were present, the use of audiovisual media most likely had an effect on the students' overall performance. Educators have the ability to assist students in developing their competencies while they are in the classroom by using audio visual media.